Essays on job search success : the roles of personality, biographical information and interviewing self-efficacy. - Lee, Swee Ling. (2008)
Applying to and interviewing with prospective employers are integral to an individual's job search for employment. Understanding the effects of individual differences on the sequential application and interview outcomes in the job search process can provide important insights for the job seeker and the recruiting organization. For the purpose of this dissertation, I address the question: How do individual difference antecedents differentially influence success in the sequential and cyclical job search process? I investigate specific job search issues in three related essays using actual job seekers and recruiting organizations in field settings.